DOI: 10.1007/978-3-540-87730-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Spider Diagrams of Order and a Hierarchy of Star-Free Regular Languages

Abstract: Abstract. The spider diagram logic forms a fragment of constraint diagram logic and is designed to be primarily used as a diagrammatic software specification tool. Our interest is in using the logical basis of spider diagrams and the existing known equivalences between certain logics, formal language theory classes and some automata to inform the development of diagrammatic logic. Such developments could have many advantages, one of which would be aiding software engineers who are familiar with formal language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Research on the language was carried out mainly (but not only) at the Visual Modelling Group (VMG) at the University of Brighton, to which the authors belong. Other logics based on spider diagrams are spider diagrams of order [11], constraint diagrams [28,43,14], generalized constraint diagrams [41] and concept diagrams [42].…”
Section: History and Overviewmentioning
confidence: 99%
“…Research on the language was carried out mainly (but not only) at the Visual Modelling Group (VMG) at the University of Brighton, to which the authors belong. Other logics based on spider diagrams are spider diagrams of order [11], constraint diagrams [28,43,14], generalized constraint diagrams [41] and concept diagrams [42].…”
Section: History and Overviewmentioning
confidence: 99%
“…al. [11]). An interpretation is a triple I = (U, < , Ψ ) where U is called the universal set and Ψ : C → PU is a function that assigns a subset of U to each contour label and < is a strict total order on U .…”
Section: Spider Diagrams Of Ordermentioning
confidence: 99%
“…al. [11]). Spider diagrams of order, D 1 and D 2 , are semantically equivalent provided they have exactly the same models.…”
Section: Spider Diagrams Of Ordermentioning
confidence: 99%
“…The proof strategy involved a model theoretic analysis of the closure properties of the model sets for the formulas of the language. In the case of spider diagrams of order, socalled becasue they provide ordering constraints on elements, it has been shown that they are equivalent to MFOL of Order [11]; MFOL[<] extends MFOL by including <, which is interpreted as a strict total order. MFOL [<] is strictly more expressive than MFOL[=] which, in turn, is strictly more expressive than MFOL.…”
Section: Introductionmentioning
confidence: 99%